Plato's Republic : a study - Rosen, Stanley, 1929-2014 (Yale University Press, 2005)
"Treating the Republic as a unity and focusing on the dramatic form as the presentation of the argument, Stanley Rosen contends that one can understand the Republic neither as a straightforward proposal for the best city nor as a cryptic repudiation of the principles upon which Socrates constructs that city. Rosen shows in detail that the Socratic principles, despite their theoretical attractiveness, could not be enacted in actual political associations, and that the attempt to do so leads sooner or later to the replacement of philosophy by ideology and justice by tyranny. There is not resolution of the split between theory and practice, even in theory. Rosen takes up in detail the technical doctrines proposed by Socrates in the Republic and shows how they are calibrated to sustain the demonstration of the instability of politics."--Provided by publisher